Interior Dalem Sasono Mulyo Dan Purwodiningratan Surakarta Dikaji Dalam Konteks Konservasi - Purnomo, Agung (Pendhapa, 2009)
The government and society should pay special attention to the existing historical and old buildings and keep them eternal. The rapid and dynamic development in every field can sometimes put forward a policy that does not support their existence. Some old buildings like Sasono Mulyo andPurwodiningratan buildings are Javanese traditional buildings existing in the milieu of Kasunanan palace of Surakarta. The interiors of the two buildings have different conditions. Some objectives of conservation among others are to return to the origin, to make use of the conserved object to support the present life, to lead the present development harmonized with the plan in the past reflected in the conversed object, and to present the history of growth/surroundings in three dimension physical appearance. Through descriptive qualitative approach, it is known that generally the condition of the interior of Sasono Mulyo is maintained more than that of Purwodiningratan. In view of the condition, it is hoped that the government and those involved pay attention to and provide funds for culturally protected buildings such as Sasonomulyo, Purwodiningratan buildings and many others. Key words: old and historical buildings, conservation, Sasono Mulyo, Purwodiningratan.